Ômega-3 em dose única venosa associado à abreviação do jejum com carboidratos em pacientes submetidos à cirurgia de revascularização do miocárdio : efeitos clínicos, metabólicos e sobre a inflamação : estudo prospectivo randomizado duplo-cego - Feguri, Gibran Roder (2018)
A strategy of limited preoperative fasting, with carbohydrate (CHO) loading and intraoperative infusion of omega-3 polyunsaturated fatty acids (ω-3 PUFA), has seldom been tried in cardiovascular surgery. Objectives: The aim of this study was to evaluate clinical variables, including morbidity (especially postoperative atrial fibrillation [POAF] and postoperative [PO] infections) and mortality; security of the method and effects on the metabolism and postoperative inflammation after coronary artery bypass grafting (CABG)/cardiopulmonary bypass (CPB) in combination, if preoperative fasts are curtailed in favor of CHO loading, and ω-3 PUFA are infused intraoperatively. Casuistic and Methods: Fifty-seven patients undergoing CABG were randomly assigned to receive 12.5% maltodextrin (200ml, 2h before anesthesia), without infusing ω-3 PUFA (CHO, n=14); water (200ml, 2h before anesthesia), without infusing ω-3 PUFA (controls, n=14); 12.5% maltodextrin (200ml, 2h before anesthesia) plus intraoperative ω-3 PUFA (0.2 g/kg) (CHO+W3, n=15); or water (200 ml, 2h before anesthesia) plus intraoperative ω-3 PUFA (0.2 g/kg) (W3, n=14). Perioperative clinical variables and mortality were analyzed, examining the need for inotropic vasoactive drugs during surgery and in ICU, as well as the PO inflammation through specific markers. Insulin resistance (IR) was evaluated by Homa-IR index and by the need of exogenous insulin. Glycemic control was evaluated by tests of capillary glucose. Results: Two deaths occurred (3.5%), but there were no instances of bronchoaspiration and mediastinitis. Neither ICU stays nor total postoperative stays differed by group (P>0.05). Patients given preoperative CHO loads (CHO and CHO+W3 groups) experienced fewer instances of hospital infection (RR=0.29, 95% CI: 0.09-0.94; P=0.023) and were less reliant on vasoactive amines during surgery (RR=0.60, 95% CI: 0.38-0.94; P=0.020). Similarly, the number of patients requiring vasoactive drugs while recovering in ICU differed significantly by group (P=0.008), showing benefits in patients given CHO loads. The overall incidence of POAF was 29.8% (17/57), differing significantly by group (P=0.009). Groups given ω-3 PUFA (W3 and CHO+W3 groups) experienced significantly fewer instances of POAF (RR=4.83, 95% CI: 1.56-15.02; P=0.001). Patients given preoperative CHO loads also got better glycemic control in the first 6h after surgery in ICU (P=0.015) and less need for exogenous insulin (P=0.018). Patients in the W3 Group presented lower values of the ultrasensitive CRP with 36 h of PO (P=0.008). The Interleukin-10 differed among groups (P=0.013), and this marker remained higher in the PO phase of patients who received ω-3 PUFA (P=0.049). Conclusion: Preoperative curtailment of fasting is safe and when implemented in conjunction with CHO loading and infusion of ω-3 PUFA during surgery, expedited recovery from CABG with CPB was observed.